OPTIMIZING PATIENT CARE EFFICIENCY: A CRITICAL REVIEW OF MEDICAL STAFF'S VITAL CONTRIBUTIONS - Mahdi Hadi Mahdi Al Yami, Mesfer Mohammed Hadi Al Sharyah, Alhassan Hadi Mohammed Al Sulaiman, Abdullah Nasser Saeed Alsalem Al Yami , Munahia Mohammed Mubarak Al Yami, Ahmed Salem Marai Al German , Fayez Mahdi Nasser Al Nasser (Chelonian Research Foundation, 2022)
The efficiency of patient care is a critical determinant of healthcare outcomes, impacting both patient satisfaction and the economic aspects of healthcare delivery. Medical staff, encompassing a broad spectrum of professionals from physicians to support personnel, play a pivotal role in shaping these outcomes. This article provides a critical review of the contributions of medical staff towards enhancing patient care efficiency. By examining current practices, identifying prevalent challenges, and highlighting innovative strategies, this review elucidates the multifaceted roles of medical staff in the context of patient care. It emphasizes the importance of a collaborative, interdisciplinary approach and the integration of technological advancements to overcome barriers and improve efficiency. Furthermore, the article discusses the influence of organizational culture, leadership, and healthcare policies on the effectiveness of patient care processes. Through a comprehensive analysis, this review aims to offer insights and recommendations for healthcare practitioners, policymakers, and administrators to optimize patient care efficiency, thereby improving healthcare outcomes and reducing unnecessary expenditures. Keywords: Patient Care Efficiency, Medical Staff Roles, Healthcare Outcomes, Interdisciplinary Collaboration, Technological Integration in Healthcare, Organizational Culture in Healthcare, Healthcare Policy and Regulation, Innovations in Patient Care